Zmeny ve slození mastných kyselin v lipidech plazmy a erytrocytů u kriticky nemocných v průbehu sepse - Novák, Frantisek; Borovská, Jirina; Vecka, Marek; Vávrová, Lucie; Kodydková, Jana; Mrácková, Magdaléna; Novák, Frantisek; Nováková, Olga; Zák, Ales (Casopis lekaru ceskych, 2010)
BACKGROUND: The overall fatty acid (FA) composition, and especially proportions of n-6 and n-3 polyunsaturated fatty acids in plasma and membrane lipids, greatly impacts on cell and organ functions as well as on many biological processes. MATERIAL AND METHODS: Polyunsaturated FA determine membrane fluidity and thus modulate activities of membrane proteins (enzymes, carriers and receptors). They also are precursors of pro- and anti-inflammatory eicosanoids and other autacoids (resolvins, protectins). Thus, alterations in lipid FA composition of critically ill patients affect reactivity of the organism to numerous pathological stimuli. The objective of this study was to analyse FA composition of plasma triacylglycerols, cholesteryl esters, plasma phospholipids and erythrocyte phospholipids in septic patients. RESULTS: The study group consisted of 30 septic patients, 19 of whom were available for three samplings: Sampling 1 was 24 hours after the onset of sepsis, Sampling 2 was 7 days after Sampling 1, and Sampling 3 was 7 days after recovery from sepsis. Eight septic patients died. Compared to healthy controls, a decrease in n-6 polyunsaturated fatty acids accompanied by increase in monounsaturated fatty acids in cholesteryl esters, plasma phospholipids and erythrocyte phospholipids persisted in all three samplings of septic patients. CONCLUSIONS: This effect of sepsis was significantly greater in cholesteryl esters and plasma phospholipids of non-surviving septic patients than in surviving ones. Moreover, non-survivors had lower proportions of n-3 polyunsaturated fatty acids in plasma phospholipids compared to survivors. The significant decrease in proportion of polyunsaturated fatty acids in lipids of septic patients in the course of sepsis reflects the severity of their critical state and supports the importance of appropriate nutritional polyunsaturated fatty acids supplementation.
Keywords: Sepsis; Humans; erytrocyty; lidé středního věku; Fatty Acids, Omega-3; sepse; Middle Aged; míra přežití; mastné kyseliny; Fatty Acids; Lipids; mužské pohlaví; omega-3 mastné kyseliny; Plasma; lipidy; Survival Rate; kritický stav; ženské pohlaví; krevní plazma; lidé; Erythrocytes; Critical Illness; Aged; senioři; Male; Female